Hubungan Biomarker Paparan Debu Tembakau (Kotinin Urin) dengan Tekanan Darah Sistolik Pekerja PTPN X, Jember - Ni Putu Desya Chandraka Dewi (Fakultas Kedokteran, 2024)
Jember, one of the largest tobacco-producing cities, requires competent tobacco processing companies like PT Perkebunan Nusantara X, the sole state-owned enterprise in the field, employing 1,698 workers. Despite its economic benefits, the tobacco industry poses health risks due to toxic substances like nicotine released into the air as dust during processing. Nicotine can be absorbed through the skin, respiratory tract, and mucous membranes, increasing cardiovascular health risks. This study aimed to investigate the relationship between tobacco dust exposure (urinary cotinine) and systolic blood pressure among workers. A cross-sectional study was conducted in October-November 2024 at PT Perkebunan Nusantara X, involving 49 workers. Sociodemographic data were collected via questionnaires, followed by blood pressure measurement and spot urine sampling to assess cotinine levels, analyzed at the Biochemistry Laboratory, Faculty of Medicine, University of Jember. Pearson correlation tests were used as both variables were normally distributed based on the Shapiro-Wilk test. Results indicated that most subjects were aged 36-45 years, predominantly married, with primary education. Most had worked over 20 years with 8-hour daily shifts, with minimal use of masks and no use of gloves. Urinary cotinine levels ranged from 59.00-140.00 ng/ml, with most systolic blood pressure readings in the high category. No significant correlation was found between urinary cotinine levels and systolic blood pressure, possibly due to variations in protective equipment use and chronic exposure leading to nAChR receptor desensitization. The study concludes no significant relationship between urinary cotinine levels and systolic blood pressure among the workers. It highlights the need for education on tobacco dust hazards and supports developing health and safety policies for sustained productivity and operational success. Keywords: Tobacco dust, Nicotine, Systolic blood pressure
Reuplod Repository Ratna 17 Juli 2026 Validasi dan Finalisasi Ratna 17 Juli 2026
Keywords: Tobacco dust; Nicotine; Systolic blood pressure